Fat-specific Protein 27 Inhibits Lipolysis by Facilitating the Inhibitory Effect of Transcription Factor Egr1 on Transcription of Adipose Triglyceride Lipase - Singh, Maneet (American Society for Biochemistry and Molecular Biology, 2014)
Lipolysis in fat tissue represents a major source of circulating fatty acids. Previously, we have found that lipolysis in adipocytes is controlled by early growth response transcription factor Egr1 that directly inhibits transcription of adipose triglyceride lipase, ATGL (Chakrabarti, P., Kim, J. Y., Singh, M., Shin, Y. K., Kim, J., Kumbrink, J., Wu, Y., Lee, M. J., Kirsch, K. H., Fried, S. K., and Kandror, K. V. (2013) Mol. Cell. Biol. 33, 3659–3666). Here we demonstrate that knockdown of the lipid droplet protein FSP27 (a.k.a. CIDEC) in human adipocytes increases expression of ATGL at the level of transcription, whereas overexpression of FSP27 has the opposite effect. FSP27 suppresses the activity of the ATGL promoter in vitro, and the proximal Egr1 binding site is responsible for this effect. FSP27 co-immunoprecipitates with Egr1 and increases its association with and inhibition of the ATGL promoter. Knockdown of Egr1 attenuates the inhibitory effect of FSP27. These results provide a new model of transcriptional regulation of ATGL.